ANALYSIS OF THE HEALTHY LIVING COMMUNITY MOVEMENT PROGRAM WHICH WAS CARRIED OUT WITHOUT ANY POLICY IN THE INDUSTRIAL AREA IN KONAWE REGENCY: HEALTHY LIVING COMMUNITY MOVEMENT PROGRAM - Desriatin Desriatin; Tasnim Tasnim; Sartini Risky; Anry Hariadhin Depu (STIKes Mandala Waluya Kendari, 2023)
Background: Based on the results of a short interview with the Konawe District Health Office Health Promotion Program, it was explained that the Healthy Living Community Movement policy had not been implemented due to many factors. One of them is the absence of a legal umbrella in the form of a district head's regulation that has been issued. Therefore the author feels interested in conducting research related to the title Analysis of Healthy Living Community Movement Activities carried out without any Policy being made in Industrial Areas in Konawe Regency Methods: Qualitative research uses a case study approach, with a triangulation method. The sample in this study consisted of Key Informants (1 person), Main Informant (5 people) and Supporting Informants (5 people), by taking samples using the QSR NVivo 12 application. Results: Informant interviews about Healthy Living Community Movement activities carried out without any policies being made in the industrial area of ​​Konawe Regency which stated that there were guidelines for implementing Healthy Living Community Movement activities, availability of budgetary, human resources and socialization of activities that were comprehensive and with the support of commitment from the government in the industrial area of ​​Konawe Regency. Conclusion: Healthy Living Community Movement activities without a Health Policy are due to the existence of guidelines for Healthy Living Community Movement implementation, budget and human resources, implementation of socialization and local government support.